Understanding iron homeostasis in MDS: the role of erythroferrone - Abba, Mohammed L.; Riabov, Vladimir; Nowak, Daniel; Hofmann, Wolf-Karsten; Boch, Tobias (Frontiers in Oncology, 2024)
Myelodysplastic neoplasms (MDS) are a heterogenous group of clonal stem cell disorders characterized by dysplasia and cytopenia in one or more cell lineages. Anemia is a very common symptom that is often treated with blood transfusions and/or erythropoiesis stimulating factors. Iron overload results from a combination of these factors together with the disease-associated ineffective erythropoiesis, that is seen especially in MDS cases with SF3B1 mutations. A growing body of research has shown that erythroferrone is an important regulator of hepcidin, the master regulator of systemic iron homeostasis. Consequently, it is of interest to understand how this molecule contributes to regulating the iron balance in MDS patients. This short review evaluates our current understanding of erythroferrone in general, but more specifically in MDS and seeks to place in context how the current knowledge could be utilized for prognostication and therapy.